Penyusunan Peraturan Desa Tentang Bale Mediasi Desa - Wardani, Trisna Kusuma; Azmussya’ni; Akhmad Muzakkir (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
This service aims to compile village regulations (Perdes) on village mediation bale. The Perdes on village mediation bale is made so that the community can solve their problems in the village realm without having to go to court, because the village mediation bale is already a legal entity and its decision is recognized in the eyes of the law. The service flow scheme is as follows: Preparation of the draft Perdes by all BPD Members of Lembuak Village - expert consultation related to law, grammar and conformity with the conditions of Lembuak Village - village deliberations attended by the Village Head, BPD, Village Officials, community leaders and representatives of each Hamlet in Lembuak Village - revision of Perdes - deliberation on determination by the Head of Lembuak Village - Socialization in each Hamlet in Lembuak Village. After the Perdes on village mediation bale is determined, then the Village Head Regulation (Perkades) on village mediation bale is also stipulated by referring to the Perdes on village mediation bale, which in this case is the full authority of the Village Head. With the regulation on village mediation bale, which will be continued by the regulation on mediation bale, it is expected to reduce the cost of the community to go to court.